The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1037/spq0000084
|View full text |Cite
|
Sign up to set email alerts
|

School climate, peer victimization, and academic achievement: Results from a multi-informant study.

Abstract: School-level school climate was examined in relation to self-reported peer victimization and teacher-rated academic achievement (grade point average; GPA). Participants included a sample of 1,023 fifth-grade children nested within 50 schools. Associations between peer victimization, school climate, and GPA were examined using multilevel modeling, with school climate as a contextual variable. Boys and girls reported no differences in victimization by their peers, although boys had lower GPAs than girls. Peer vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 79 publications
(153 reference statements)
9
98
1
9
Order By: Relevance
“…As the Kowalski et al (2014) review highlights, youngsters' perception of school climate is a risk factor for cyber victimization, that is, a perceived negative school climate is associated with cyber victimization. This result is supported by Wang et al (2014) in a study of 1023, 5 grade American students, who found a relationship between cyber victimization and a negative school climate. School safety: Kowalski et al (2014) found that cyber victimization is related to a low perception.…”
Section: School Risk Factorssupporting
confidence: 81%
See 1 more Smart Citation
“…As the Kowalski et al (2014) review highlights, youngsters' perception of school climate is a risk factor for cyber victimization, that is, a perceived negative school climate is associated with cyber victimization. This result is supported by Wang et al (2014) in a study of 1023, 5 grade American students, who found a relationship between cyber victimization and a negative school climate. School safety: Kowalski et al (2014) found that cyber victimization is related to a low perception.…”
Section: School Risk Factorssupporting
confidence: 81%
“…Similarly, Wang et al (2014) in their study with 1.023 5 th grade students and in the review of 25 studies conducted by Tokunaga (2010) it was found that cybervictimization is associated with students' low academic achievement. This risk factor can be considered dynamic, since can change over time.…”
Section: Low School Achievementmentioning
confidence: 88%
“…There is a need to expand this ecological view of school climate to clarify targets for improving the safety of our schools (Manvell, 2012) and the impact of positive school climate on child outcomes. Consistent with a growing body of research (Espelage et al, 2014;Leadbeater et al, 2014;Wang et al, 2014), our findings suggest that working to improve school relationships between students and teacher and students themselves, and to enhance students' experiences of fairness and equity in sharing resources may be key to improving children's social, emotional, and behavioral outcomes. Active responses on the part of school staff that support victimized children and their families are crucial to stop the escalating negative school climate perceptions that can preoccupy withdrawn children who may feel marginalized from school activities.…”
Section: Limitations and Conclusionsupporting
confidence: 81%
“…climate is seen in research showing that poor school climate is associated with low academic performance (Brand et al, 2003, Wang et al, 2014, school avoidance (Brand et al, 2003;Welsh, 2000), youth delinquency (Welsh, 2000), substance abuse (Brand et al, 2003), victimization (Welsh, 2000, depression and low self-esteem (Brand et al, 2003;Way, Reddy, & Rhodes, 2007, Gendron, Williams, & Guerra, 2011, bullying (Nansel et al, 2001, Gendron et al, 2011, Wang et al, 2014, and greater behavior problems and risk behaviors in general (Bear, Gaskins, Blank, & Chen, 2011;Hopson & Lee, 2011;Klein et al, 2012).…”
Section: │3mentioning
confidence: 99%